Case Report: Interventricular septal hematoma after ventricular septal defect repair with persistent left ventricular communication: 10-year follow-up - Anna Rudek-Budzyńska; Aleksandra Morka; Tomasz Mroczek (Frontiers in Cardiovascular Medicine, 2026)
Interventricular septal hematoma is a rare complication of congenital heart surgery with unpredictable clinical course and limited data guiding management. We report a female infant who developed a giant interventricular septal hematoma after surgical closure of a perimembranous ventricular septal defect at 4 months of age. Early postoperative imaging demonstrated a large intraseptal cavity without ventricular communication, followed by development of multiple small fistulous connections with the left ventricular lumen one month later. Cardiac magnetic resonance imaging confirmed an extensive blood-filled cavity involving the basal, mid and apical interventricular septum, with preserved global ventricular systolic function. Serial multimodality imaging over 10 years demonstrated stable hematoma morphology and persistent communication with the left ventricle without hemodynamic compromise. Conservative management was maintained; however, ischemic stroke occurred five years after surgery, requiring long-term anticoagulation. This case represents the longest reported follow-up of interventricular septal hematoma with persistent left ventricular communication and provides insight into the natural history of this rare entity, demonstrating that long-term structural stability and preserved ventricular function may be achieved under non-interventional management despite the risk of thromboembolic complications.